THE CORRELATION BETWEEN EATING DISORDERS AND POST-PARTUM DEPRESSION IN WOMEN (CIPEEX, 2024)
The post-partum period of a mother’s life is a complex and vulnerable time, for both the patient and the child’s health, and requires risk factors screening for puerperal disorders. Hence, this study proposes to discuss the relevance of eating disorders (ED) in predicting and treating post-partum depression (PPD). It is a review of literature, analyzing 9 original articles found in Medical Literature Analysis and Retrieval System Online (MEDLINE) and Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS) databases in the last 5 years, including only theme-relevant and original full-text articles. The keywords used in this research are the MeSH terms: post-partum depression, eating disorder, puerperal disorders. The analysis of all chosen articles resulted in two main topics of discussion. The first one includes a discussion on ED history, before the pregnancy or during pregnancy, as a very relevant risk factor for developing post-partum depression. It was shown by multiple studies that both ED and PPD development during the post-natal period is induced by weight and humor fluctuations, body changes and exercising limitations. It is also a consensus between studies that all mental disorders previous to the pregnancy, including EDs, are risk factors for developing PPD in these women. The second topic of discussion addresses EDs as an unprecedented comorbidity to PPD in women, supported by several studies in this review, due to body image and weight concerns in women during pregnancy and after delivery. It was noted that behaviors such as binge eating, purging, excessive dieting and exercising were higher in this group of women, highlighting that the post-natal period exposes women to a high risk of developing EDs. Therefore, eating disorders is an incredibly important risk factor and/or comorbidity to developing post-natal depression, and its identification and appropriate treatment is substantial to the mother and the child’s health outcomes. Thus, it is necessary that disordered eating, body image concerns and depressive symptoms are always closely monitored through regular appointments and the administration of screening scales, before, during and after pregnancy, as a way of refrain from developing eating disorder and/or post-partum depression.
Keywords: Post-partum depression; eating disorder; puerperal disorders